2002
DOI: 10.1063/1.1485305
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transparency ramp-type Josephson contacts through interlayer deposition

Abstract: A thin interlayer is incorporated in ramp-type Josephson junctions to obtain an increased transparency. The interlayer restores the surface damaged by ion milling and has the advantage of an all in situ barrier deposition between two superconductors, leading to clean and well-defined interfaces. The method has been applied to Josephson junctions between high (YBa2Cu3O7−δ) and low temperature (Nb) superconductors, separated by a Au barrier. Transmission electron microscopy images of these junctions reveal cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…After etching the ramp and cleaning of the sample, a 7 nm YBa 2 Cu 3 O 7−δ interlayer is deposited, the function and properties of which are described in Ref. 13, followed by the in-situ pulsed-laser deposition of a Au barrier-layer of 12 nm for the 1D array samples and 20 nm for the 2D array samples. A 160 nm Nb counter electrode is then formed by dc sputtering and structured by lift-off.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After etching the ramp and cleaning of the sample, a 7 nm YBa 2 Cu 3 O 7−δ interlayer is deposited, the function and properties of which are described in Ref. 13, followed by the in-situ pulsed-laser deposition of a Au barrier-layer of 12 nm for the 1D array samples and 20 nm for the 2D array samples. A 160 nm Nb counter electrode is then formed by dc sputtering and structured by lift-off.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recently a technology that allows for photolithographic fabrication of π-shift devices and arrays of great complexity, using YBa 2 Cu 3 O 7−δ -AuNb (YBCO-Au-Nb) ramp-edge tunneling junctions has been demonstrated. 12,13 Moreover, it has recently been demonstrated that π-rings can also be fabricated using Josephson junctions with ferromagnetic layers in the tunnel barriers. 14,15,16 In this paper we report on experiments in which the YBCO ramp-edge technology was used to fabricate large arrays of π-rings.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a 140 nm Nb layer was deposited by dc sputtering. Fabrication of these junctions [14] as well as Josephson tunneling in these systems [13] have been reported elsewhere. Measurements of the Josephson critical current versus a magnetic field applied either perpendicular or parallel to the c-axis, strongly suggests that electrical transport in these junctions occur essentially in the ab plane alone, so that the c-axis coupling may be neglected.…”
Section: Tunneling Experiments In Ybco/au/nb Junctionsmentioning
confidence: 99%
“…For the preparation of YBCO/Au/Nb ramp junctions (see Fig.1 [14]. Then, a 6 nm YBCO interlayer was prepared, providing for a high-quality interface to the subsequently in situ deposited Au-barrier layer.…”
Section: Tunneling Experiments In Ybco/au/nb Junctionsmentioning
confidence: 99%
“…Part of the difference between the pn, pp ′ n and pn ′ n configurations can be explained by two effects. Firstly, a restoring effect of the growth of near lattice-matched Nd 1.8 Ce 0.2 CuO 4 on the NCCO electrode before the deposition of the LSCO electrode, that can recrystallize some of the damaged areas created by the argon ion milling [137]. Secondly, the strength of the strain in the LSCO layer, i.e.…”
Section: Effect Of Different Interlayersmentioning
confidence: 99%